A Healthy Lifestyle Offsets the Increased Risk of Childhood Obesity Caused by High Birth Weight: Results From a Large-Scale Cross-Sectional Study - Wang, Zheng-he; Zou, Zhi-yong; Dong, Yan-hui; Xu, Rong-bin; Yang, Yi-de; Ma, Jun (Frontiers in Nutrition, 2021)
Objective To investigate whether a healthy lifestyle is associated with lower childhood obesity regardless of birth weight. Methods Participants were selected from a large-scale cross-sectional study conducted in seven provinces across China. Birthweight and lifestyle factors were collected through a questionnaire. A weighted healthy lifestyle score was calculated and categorized into favorable, intermediate, and unfavorable lifestyle. Results A total of 47,768 participants were enrolled into this study. Overall, 16.4% of participants followed a favorable lifestyle, 62.8% followed an intermediate lifestyle, and 20.8% followed an unfavorable lifestyle. Compared with participants born normal birth weight (NBW), participants born high birth weight (HBW) (OR=1.58; 95%CI: 1.48-1.77) and very high birth weight (VHBW) (OR=1.79; 95%CI: 1.47-2.18) had higher obesity risk, however, participants born low birth weight (LBW) had lower obesity risk (OR=0.81; 95%CI: 0.68-0.96). Participants with an unfavorable lifestyle was associated with a higher risk of childhood obesity compared with of participants with favorable lifestyle (OR=1.25; 95%CI: 1.14-1.38). Participants born VHBW and with an unfavorable lifestyle had 2.76 times (95%CI: 1.78-4.28) risk of childhood obesity compared with participants born NBW and with a favorable lifestyle. However, adherence to a favorable lifestyle seems to counteract the elevated risk of childhood obesity by VHBW (OR= 1.37; 95%CI: 0.84-2.24). Conclusion Both HBW and unfavorable lifestyle were significantly associated with childhood obesity risk. Adherence to a favorable lifestyle decreased risk of childhood obesity among participants with VHBW. More longitudinal study is need to repeat the finding to inform tailored prevention programs.